Experimental Investigation of the Cooling Effect Generated by a Heat Sink Integrated Thermoelectric-Based U-Shaped Air-Conditioning System - Yesha Patel (MDPI AG, 2021)
Over the past years, thermoelectric refrigeration has attracted considerable attention due to its compact size, reliability, and environmental friendliness. Traditional refrigeration systems use greenhouse gases, which significantly impacts our environment. Therefore, in this work, a thermoelectric cooler prototype refrigeration system, a solid-state device causing no harm to the environment, was constructed and tested experimentally. A heat sink was attached to the cold side of the thermoelectric cooler (TEC) to cool the air passing through the heat sink. In contrast, a cold plate was attached to the hot side of TEC to remove the generated heat with the help of the liquid circulating in the aluminium cold plate. Experiments were carried out by varying parameters such as input current to the TEC module, inlet air flow rate, water flow rate through the cold plate, etc. The experimental results indicate that the cooling effect is increased by approximately 40%, increasing current from 2A to 8A. However, the cooling effect was decreased with increasing inlet airflow rate by 58% when airflow rate increased from 2.25 m/s to 3.55 m/s. However, the system performance shows approximately 35% increment with an increase in fan speed. Furthermore, a decrease in the water flow rate from 3.04 L/m to 1.80 L/m showed a slight increment in the cooling by 15%.